Association between Rab31/rs9965664 polymorphism and immunoglobulin therapy resistance in patients with Kawasaki disease - Yu, Hongyan; Lin, Yueling; Xu, Yufen; Chen, Kaining; Wang, Yishuai; Fu, Lanyan; Zhou, Huazhong; Pi, Lei; Che, Di; Qiu, Xiantao; Gu, Xiaoqiong (Frontiers in Cardiovascular Medicine, 2022)
Background Kawasaki disease (KD) is an acute febrile systemic vasculitis affecting infant and young children. High dose of Intravenous immunoglobulin (IVIG) is the first line strategy for KD patients to reduce persist inflammation and the risk of coronary artery aneurysms (CAA) formation. Unfortunately, 10-20% of the patients had no response to the treatment and was defined as resistant to IVIG. Rab31 has been reported regulating innate immunity in several human diseases. However, whether single nucleotide polymorphism (SNP) of Rab31 gene predispose to IVIG therapy response in KD were uncovered. Methods Rab31/rs9965664 polymorphism was genotyped in 1024 Chinese KD patients through TaqMan assay. The odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to assess the strength of association between Rab31/rs9965664 polymorphism and IVIG therapeutic effects. Results Our results showed that Rab31/rs9965664 AA/GA genotype was significantly associated with increased risk to IVIG resistance compared to GG genotype (GA versus GG: P=0.0249; AA versus GG: P=0.0016; AA/GA versus GG: P=0.0039; and AA versus GG/GA: P=0.0072). Moreover, the KD individuals carrying the rs9965664 A allele displayed lower Rab31 protein levels, consisted with the expression level of Rab31 in IVIG resistant group was decreased significantly compare to the response group. Mechanical study demonstrated Rab31 modulated IVIG response through NLRP3 and p38 pathway. Conclusion These results suggested that Rab31/rs9965664 polymorphism might be associated with increased risk of IVIG resistance in southern Chinese KD patients. And the possible mechanism is Rab31 regulates NLRP3 pathway negatively to inhibit IVIG response.